A multi-agent framework for research supervision management - Jassim O.A.; Mahmoud M.A.; Sharifuddin M. (Springer Verlag, 2023)
Artificial intelligence; Intelligent agents; Multi agent systems; Software agents; Agent-based framework; General applications; Intelligent software agent; Multiagent framework; Research development; Research supervisions; Student performance; Task management; Research and development management